Diagnostic performance of contrast-enhanced ultrasound and magnetic resonance imaging for detecting colorectal liver metastases: A systematic review and meta-analysis. Issue 9 (September 2019) - Zhang, Luni; Zhang, Li; Wang, Hui; Chen, Libo; Sui, Guoqing
Abstract: Objectives: To determine the diagnostic performance of contrast-enhanced ultrasound, diffusion-weighted magnetic resonance imaging and contrast-enhanced magnetic resonance imaging for detecting colorectal liver metastases. Methods: We performed comprehensive searches of the MEDLINE, EMBASE, and Cochrane Library databases to identify studies reporting the per-lesion diagnostic accuracy of contrast-enhanced ultrasound, diffusion-weighted magnetic resonance imaging, and contrast-enhanced magnetic resonance imaging for detecting colorectal liver metastases. Studies published between January 2003 and December 2018 with reference standards, including histopathology and intraoperative observation, and/or follow-up, were included. Sources of bias were assessed using the QUADAS-2 tool. A linear mixed-effects regression model was used to determine sensitivity estimates. Results: Overall, 47 articles were included. The sensitivity estimates for contrast-enhanced ultrasound, diffusion-weighted magnetic resonance imaging, and contrast-enhanced magnetic resonance imaging for detecting colorectal liver metastases were 85.3%, 83.0%, and 90.1%, respectively. For lesions ≥10 mm in diameter, the sensitivities were 93.1%, 92.9%, and 94.5%, respectively. In 21 articles using histopathology as the only reference standard, the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio for contrast-enhanced ultrasound/contrast-enhanced magnetic resonance imaging were 86%/91%, 91%/95%, 9.2/16.6, 0.15/0.10, and 61/170, respectively. Conclusions: CEUS showed a diagnostic ability comparable to that of DWI and CEMRI, particularly for lesions ≥10 mm in diameter.